The Deer Hunter : essai de topologie imaginaire américaine - Jacques Pothier (Anglophonia)
This essay centers on Michael Cimino’s film on the Vietnam War to explore how the mythology of space in the American imagination is revisited at the end of the twentieth century. In this film the dichotomies between civilization/the wilderness, male space / female territory, national vs. ethnic identities present in the American imagination from Cooper to the classic western through Washington Irving or Mark Twain, are thoroughly revisited through the tragic counterpointing of a Russian working-class community in a Pennsylvania small town and an Asian heart of darkness. Cimino’s heroes find out that the otherness of evil may turn out to be very familiar--but in the end the lid is back on Pandora’s box.